2017
DOI: 10.1186/s12940-017-0346-x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ambient air pollution and calcification of the mitral annulus and aortic valve: the multi-ethnic study of atherosclerosis (MESA)

Abstract: BackgroundLong-term exposure to high ambient air pollution has been associated with coronary artery calcium (CAC), a marker of cardiovascular disease (CVD). Calcifications of left-sided heart valves are also markers of CVD risk. We investigated whether air pollution was associated with valvular calcification and its progression.MethodsWe studied 6253 MESA participants aged 45–84 years who underwent two cardiac CT scans 2.5 years apart to quantify aortic valve calcium (AVC) and mitral annular calcium (MAC). CAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Consistent with the findings of a multiethnic study, 40 we found an ambiguous association between PM 2.5 and valvular heart disease, suggesting that PM 2.5 might play a less important role than other primary risk factors such as genetics, infections, and other cardiovascular conditions. 41 The ambiguous association could also result from data variability.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the findings of a multiethnic study, 40 we found an ambiguous association between PM 2.5 and valvular heart disease, suggesting that PM 2.5 might play a less important role than other primary risk factors such as genetics, infections, and other cardiovascular conditions. 41 The ambiguous association could also result from data variability.…”
Section: Discussionsupporting
confidence: 90%
“…4,[6][7][8] In this connection, several groups of investigators have reported that there is a strong link between adverse health outcomes including mortality and hospitalization and exposure to air pollution. [9][10][11] Air pollution exposure during pregnancy is a potential health threat to the unborn child as the pollutants might pass through placenta and affect the developing foetus. 12,13 Previous studies suggested that exposure to air pollution during pregnancy was linked to behavioural and neuroanatomical abnormalities in the offspring, including impaired intellectual ability, reduction of brain white matter and increased risk of attention deficit/hyperactivity disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Pollutants of air pollution also include gaseous substances, namely ozone, nitrogen oxides and sulphur dioxide . In this connection, several groups of investigators have reported that there is a strong link between adverse health outcomes including mortality and hospitalization and exposure to air pollution . Air pollution exposure during pregnancy is a potential health threat to the unborn child as the pollutants might pass through placenta and affect the developing foetus .…”
Section: Introductionmentioning
confidence: 99%
“…Air quality and exposures are important environmental contributors that affect both the morbidity and mortality of the population. 2,3 Studies have focused on the effect of air quality on outcomes such as asthma, 4,5 atherosclerosis, 6,7 obesity, 8 metabolic syndromes 9,10 and other cardiopulmonary disorders. According to the WHO, 4.2 million premature deaths worldwide per year are attributed to air quality and pollution.…”
Section: Introductionmentioning
confidence: 99%